The Role Of Digital Education In The Formation Of Professional Skills - Urinov Khushnudjon Abdulomitovich (Periodica Journal, 2024)
Today, digital technologies are rapidly developing and entering every aspect of social life. In particular, modern information technologies in the field of education have a positive effect on the quality of education. This article discusses the importance of digital education in the formation of professional skills. Analytical information on the role of digital technologies in the field of education of Uzbekistan and the development of professional competences of digital education is provided.
Keywords: vocational education; literacy rate; digital education